Indications of Biased Risk Adjustment in the Hospital Readmission Reduction Program. Issue 1 (January 2015) - Fuller, Richard L.; Atkinson, Graham; Hughes, John S.
<x xml:space="preserve">Abstract</x> The Centers for Medicare and Medicaid Services hospital readmission reduction program administers substantial penalties to hospitals with excess readmissions. In our analysis of Medicare claims data, we find hospitals with the highest percentages of patients with several chronic conditions and advanced age have excess readmission ratios that are overstated because of inadequate risk adjustment. The distribution of chronic conditions and age is sufficient to cause 4.5% (heart failure), 6.2% (pneumonia), and 13.8% (acute myocardial infarction) of high disproportionate share hospitals to inappropriately receive penalties out of keeping with the intent of the hospital readmission reduction program. We believe that the risk adjustment model underlying the HRRP requires urgent independent review.